Recollection reduces unitised familiarity effect. Issue 4 (20th April 2016) - Shao, Hanyu; Opitz, Bertram; Yang, Jiongjiong; Weng, Xuchu
Abstract : Two types of encoding tasks have been employed in previous research to investigate the beneficial effect of unitisation on familiarity-based associative recognition (unitised familiarity effect), namely the compound task and the interactive imagery task. Here we show how these two tasks could differentially engage subsequent recollection-based associative recognition and consequently lead to the turn-on or turn-off of the unitised familiarity effect. In the compound task, participants studied unrelated word pairs as newly learned compounds. In the interactive imagery task, participants studied the same word pairs as interactive images. An associative recognition task was used in combination with the Remember/Know procedure to measure recollection-based and familiarity-based associative recognition. The results showed that the unitised familiarity effect was present in the compound task but was absent in the interactive imagery task. A comparison of the compound and the interactive imagery task revealed a dramatic increase in recollection-based associative recognition for the interactive imagery task. These results suggest that unitisation could benefit familiarity-based associative recognition; however, this effect will be eliminated when the memory trace formed is easily accessed by strong recollection without the need for a familiarity assessment.